Procedures and functions manual for the administrative support section of the post- grade and research sub-direction in the UPEL-IPB (Revista Electrónica REDINE, 2018)
The current research got framed as special project, supported on a descriptive field-research, whose purpose was to propose a procedures and functions manual for the administrative support section of the post-grade and research sub-direction in the UPEL-IPB, as a goal of satisfying a real need of the university, such as standardizing the administrative procedures. The study subjects were seven workers who work in this section: a chief teacher, four members who belong to the professional administrative staff, and two ordinary administrative. A instrument, with a dichotomist scale was applied which was valid under the Expert Judgment. The results were tabulated and shown trough graphics and charts. This study allowed concluding that it is necessary to propose procedures and functions manual for the administrative support section of the post- grade and research sub-direction in the UPEL-IPB.
Keywords: functions manual; administrative procedures; supporting section